2022
DOI: 10.3390/ijms23169212
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bioenergetics in Neurodegeneration

Abstract: Bioenergetic and mitochondrial dysfunction are common hallmarks of neurodegenerative diseases. Decades of research describe how genetic and environmental factors initiate changes in mitochondria and bioenergetics across Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS). Mitochondria control many cellular processes, including proteostasis, inflammation, and cell survival/death. These cellular processes and pathologies are common across neurodegenerative diseases. Eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 114 publications
0
10
0
Order By: Relevance
“…Therefore, brain energy demand is mostly met by the metabolism of glucose [ 162 ]. Bioenergetic and mitochondrial dysfunction are common hallmarks of PD and ALS, and regulate disease onset and progression [ 161 , 163 , 164 ]. In ALS pathogenesis, the early dysregulation of the AMPK signaling pathway was found in motor neurons and in a large proportion of patients [ 165 ].…”
Section: α 1 -Ar Antagonistsmentioning
confidence: 99%
“…Therefore, brain energy demand is mostly met by the metabolism of glucose [ 162 ]. Bioenergetic and mitochondrial dysfunction are common hallmarks of PD and ALS, and regulate disease onset and progression [ 161 , 163 , 164 ]. In ALS pathogenesis, the early dysregulation of the AMPK signaling pathway was found in motor neurons and in a large proportion of patients [ 165 ].…”
Section: α 1 -Ar Antagonistsmentioning
confidence: 99%
“…These investigations have opened application areas in artificial light harvesting, 5 as biomarkers for cardiovascular diseases and cancer cells, 6,7 and more recently in brain sciences. 8 One of the first breakthroughs in understanding how energy is transferred in biology came from the discovery of chemiosmotic coupling. It described how electrochemical gradients can be employed to store energy in cells by the use of light-or chemical-driven ion pumps.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recent studies have indicated that in neurodegeneration, phytochemical intervention, i.e., resveratrol and EGCG, is caused by aging and immunoregulatory insults. EGCG’s ability to reduce microglial activation, mitochondrial dysfunction, and oxidative stress in neurodegenerative disease correlates to its unique structure and bioenergetic capabilities [ 24 , 25 ]. EGCG has displayed neuroprotective ability in halting Aβ formation and accumulation.…”
Section: Introductionmentioning
confidence: 99%